Eclipsing Stalin: The GULAG History Museum in Moscow as a Manifestation of Russia's Official Memory of Soviet Repression - Zavadski, Andrei; Dubina, Vera (Problems of post-communism, 2023)
This article analyzes the temporary (2015) and permanent (2018) expositions of Moscow's GULAG History Museum (GHM), and the documents surrounding its creation. The analysis demonstrates two key findings. First, focusing on the Gulag and omitting post-Gulag Soviet repression, the GHM ultimately works to historicize the former. Second, while prominently ending the permanent exposition with Stalin's death, the GHM nevertheless downplays his role in the repression. The Gulag becomes a thing of the past, something to acknowledge--and leave behind. Stalin, however, is extracted from that past: he remains in the present, as part of the official "Great Patriotic War" memory.